Infective Endocarditis, a Rare Complication of Late Neonatal Group B Strep Sepsis - McLennan, Daniel; Morgan, Gareth (Frontiers in Pediatrics, 2018)
Background: Infective endocarditis (IE) is extremely rare in infants with structurally normal hearts. We present a case of Group B Streptococcus (GBS) endocarditis in a 5 week old. Clinical case: a 5-week old male presented to his local hospital with fever and was diagnosed with GBS sepsis. He received four days of intravenous antibiotics and was discharged home with six days of oral antibiotics. He re-presented five days after discharge with severe sepsis as well as a new pathological pan systolic murmur and was diagnosed with IE following echocardiographic identification of a mitral valve vegetation. He was subsequently transferred to a tertiary cardiology center. Ten days after readmission he developed an intracranial hemorrhage associated with rupture of a mycotic aneurysm requiring emergency evacuation. Conclusion: Late onset GBS sepsis is rare, but when improperly treated can have severe consequences. Infant IE is extremely rare. When diagnosed prompt treatment must be initiated to provide the best outcome for the patient, including consideration for surgical removal of the infective lesion.